Cheating death - Cotter, Carol; Soetenga, Everett; Hennick, Michael (Wisconsin Educational Television Network and WHA-TV [producer] ; Educational Media Australia [distributor], 1992)
SUMMARY: This film explores and discusses research on the human aging process and the implications for society if this process could be slowed down. Attitudes to death are also discussed.